Karyotype analysis of Common Cocklebur (Xanthium strumarium L.) - Dogan, Gulden; Kiran, Yasar (Zafer AKAN [EN], 2017)
Objective: The purpose of this study is to determine the mitotic chromosome number, morphometric parameters, and karyotypes of Xanthium strumarium and make contributions to other multidisciplinary studies on the genus. Material and Methods: The seeds were germinated on moist filter paper in Petri dishes at 25°C. Actively growing root tips were pre-treated with aqueous paradichlorobenzene for 4h at room temperature. Then, the root tips were fixed with acetic alcohol (1:3 glacial acetic acid–absolute ethanol) for at least 24 h at 4°C, hydrolysed in 1 N HCl at 60°C for 3 min, then rinsed in tap water for 3–5 min. Finally, they were stained in Feulgen for 1 h and mounted in 45% acetic acid. Digital microphotographs from at least five well-spread metaphase plates were taken using an Olympus BX51 microscope and were recorded with an Olympus Camedia C-4000 digital camera.Results: The chromosome number is determined as 2n = 36 for this taxon. The karyotype consists of 16 median region (m) and 2 submedian region (sm) chromosomes. The metaphase chromosome length ranges from 2.30 to 4.03 ?m, longest to shortest chromosome ratio is 1.7:1.1, total karyotype length (TKL) 54.76 ?m and the karyotype symmetry is type 1A. Conclusion: The results of this study showed that the chromosome number of Xanthium strumarium is 2n=36. Satellites were not observed in the karyotype of this species. Identifying the chromosome number of this species in this study provides a base for biosystematic studies.